2013
DOI: 10.1603/me12162
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression of Tissue-Specific Molecules in Ex vivoDermacentor variabilis(Acari: Ixodidae) During Rickettsial Exposure

Abstract: Ticks serve as both vectors and the reservoir hosts capable of transmitting spotted fever group Rickettsia by horizontal and vertical transmission. Persistent maintenance of Rickettsia species in tick populations is dependent on the specificity of the tick and Rickettsia relationship that limits vertical transmission of particular Rickettsia species, suggesting host-derived mechanisms of control. Tick-derived molecules are differentially expressed in a tissue-specific manner in response to rickettsial infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…As in previous reports (10), the transcriptomics and proteomics results showed differences between cultured tick cells and tick developmental stages and adult tissues in response to pathogen infection, highlighting the presence of tissue-specific differences in the tick cell response to infection (8,12,67). Furthermore, the results of this study are probably relevant for the characterization of the response of tick hemocytes to A. phagocytophilum infection (50,51).…”
Section: Discussionsupporting
confidence: 81%
“…As in previous reports (10), the transcriptomics and proteomics results showed differences between cultured tick cells and tick developmental stages and adult tissues in response to pathogen infection, highlighting the presence of tissue-specific differences in the tick cell response to infection (8,12,67). Furthermore, the results of this study are probably relevant for the characterization of the response of tick hemocytes to A. phagocytophilum infection (50,51).…”
Section: Discussionsupporting
confidence: 81%
“…However, variables exist that may affect organ viability and TBFV replication in organs, such as bloodfeeding and the virus concentration used for infection. Unfed female tick organs were utilized for this study (as in the study by Sunyakumthorn et al [78]); thus, results may reflect a bias to a specific adult tick sex (or tick life stage) and physiological state. In vivo studies with TBEV in Ixodes ricinus ticks have shown higher levels of TBEV replication in blood-fed versus unfed ticks and, in particular, greater replication in salivary glands (60).…”
Section: Discussionmentioning
confidence: 99%
“…GST proteins are considered as common 'housekeeping' genes forming a large protein superfamily present in eukaryotes and prokaryotes [64]. They function as detoxifying enzymes and thus in ticks may function in response to acaricides or in response to tick-borne pathogens and or stress [65,66].…”
Section: Intracellular Antigensmentioning
confidence: 99%